Physicochemical characteristics of unripe and ripe banana 'FHIA 18' submitted to phosphorus fertilizer over three production cycles - Batista Bolfarini, Ana Carolina [UNESP]; Azevêdo Souza, Jackson Mirellys [UNESP]; Putti, Fernando Ferrari [UNESP]; De Souza Silva, Marcelo [UNESP]; Ferreira, Rafael Bibiano [UNESP]; Leonel, Magali [UNESP]; Tecchio, Marco Antonio [UNESP]; Leonel, Sarita [UNESP] (Universidade Estadual de Londrina, 2020)
The banana fruits of 'FHIA 18' have sensory properties like the 'Prata' ones. However, there is no information regarding to phosphorus (P) requirement of this hybrid and its effects on postharvest quality. This study aims to evaluate the physicochemical properties of 'FHIA 18' banana fruits submitted to different phosphorus levels under the edaphoclimatic conditions of the municipality of São Manuel, state of São Paulo, during three successive production cycles. Therefore, different levels of Phosphorus (0 [0%], 20 [50%)], 30 [75%], 40 [100%], 50 [125%] and 60 kg ha-1 year-1 P2O5 [150%]) were applied during three production cycles. A completely randomized design and split plot structure was used, the plots consisted of six phosphorus fertilizers doses and three production cycles (2014, 2015 and 2016) in sub plots. For unripe fruits, we evaluated the contents of dry matter, starch, total sugars, reducing sugars and phosphorus. For ripe fruits, we analyzed firmness, peel colour descriptors, total titratable acidity, total soluble solids, maturity index, total sugars and reducing sugars. Results showed that P fertilizer provided an increase in P content in unripe fruits until the application of 100% of the recommended dose; besides an increase in the reducing sugar contents until the application of 61% over the first production cycle. Results also indicated that applying lower phosphorus doses (<100% of the recommended dose) promoted lower total titratable acidity and higher maturity index (52-53% of recommendation) in ripe fruits. Regardless of P2O5 dose, the contents of dry matter, starch and phosphorus increased in unripe fruits from first to third crop cycle, as well as the firmness, total soluble solids contents, maturity index and sugar content in ripe fruits.
Keywords: Maturation index; Mineral nutrition; Musa spp; P2O5; Starch